An empirical analysis: The impact of project-based learning on students' mathematical reflective thinking skills and self-concept - Noer, Sri Hastuti; Triana, Mella; Gunowibowo, Pentatito; Asnawati, Rini; Vetama, Wanda (Universitas Islam Negeri Raden Intan Lampung, 2024)
Mathematical reflective thinking skills and self-concept are essential aspects of 21st-century learning to address global challenges. This study analyzes the effect of Project-Based Learning (PjBL) on students' mathematical reflective thinking skills and self-concept. The experimental research involved 75 tenth-grade students in Bandar Lampung using a posttest control group design. Data were collected through mathematical reflective thinking skills tests and self-concept questionnaires and analyzed using parametric and non-parametric statistical tests. The results showed that the implementation of PjBL did not significantly affect students' mathematical reflective thinking skills and self-concept compared to conventional learning. However, the indicators of mathematical reflective thinking skills achievement in the PjBL class were higher. This study implies the need for a longer implementation of PjBL to achieve significant results and its potential contribution to developing students' collaboration, creativity, and social skills as part of holistic learning.